Unexpected Improvement of Hand Motor Function with a Left Temporoparietal Low-Frequency Repetitive Transcranial Magnetic Stimulation Regime Suppressing Auditory Hallucinations in a Brainstem Chronic Stroke Patient - Thomas, Fanny; Bouaziz, Noomane; Amengual, Julià L.; Andrianisaina, Palmyre Schenin-King; Gaudeau-Bosma, Christian; Moulier, Virginie; Valero-Cabré, Antoni; Januel, Dominique (Frontiers in Psychiatry, 2017)
We here report paradoxical hand function recovery in a 61-year-old male tetra-paretic chronic patient following a stroke of the brainstem (with highly degraded right and abolished left hand finger flexion/extension disabling him to manipulate objects) who experienced insidious auditory hallucinations (AHs) 4 years after such event. Symptomatic treatment for AHs was provided with periodical double sessions of low-frequency rTMS (daily 1Hz, 2x1200 pulses interleaved by 1h interval) delivered to the left temporo-parietal junction across two periods of 5 weeks and 3 weeks, respectively. At the end of each stimulation period, AHs disappeared completely. Most surprisingly and totally unexpectedly, the patient experienced beneficial improvements of long-lasting impairments in his right hand function. Detailed examination of onset and offset of rTMS stimulation regimes strongly suggests a temporal relation with the remission and re-appearance of AHs and also with a fragile but clinically meaningful improvements of right (but not left) hand function contingent to the accrual of stimulation sessions. On the basis of post-recovery MRI structural and functional evidence, mechanistic hypotheses that could subtend such unexpected motor recovery are critically discussed.